Pengaruh Diferensiasi Produk Dan Nilai Emosional Terhadap Loyalitas Konsumen Pada Syaksha Shisha Malang - Muhammad Rifqy; Muhammad Ridwan Basalamah; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to examine the effect of product differentiation and emotional value on consumer loyalty at Syaksha Shisha Malang. The population in this study is all customers of Sarijan Café accumulated in a month totaling 800 customers. The sampling technique used purposive sampling method with a total sample of 89 respondents. The analytical method used is multiple linear regression analysis using the IBM SPSS 25 (Statistical Product and Service Solutions) application tool. Based on testing using the simultaneous F test analysis, the results showed that there was a significant influence between variable X (product differentiation, emotional value) simultaneously on variable Y (consumer loyalty) on Syaksha Shisha Malang customers, and analysis of the partial t test results showed that product differentiation has a positive and significant effect on consumer loyalty Syaksha Shisha Malang with a significance value of 0.008 <0.05, emotional value has a positive and significant effect on consumer loyalty Syaksha Shisha Malang with a significance value of 0.000 <0.05. Keywords: Product Differentiation, Emotional Value, Consumer Loyalty.